Resistance of Musca domestica L. populations to cyromazine (insect growth regulator) in Brazil - Mara Cristina Pinto; Angelo Pires do Prado (Memorias do Instituto Oswaldo Cruz, 2001)
Five field populations of Musca domestica L. collected in poultry farms were bioassayed in order to detect possible resistance to the larvicide cyromazine in Brazil. The concentrations used were 0, 0.5, 0.1, 0.2, 0.4, 1, 2, 4 and 8 ppm. Three populations (Petrópolis, RJ, Montes Claros, MG and Promissão, SP) were resistant, while the other two populations (Ibiuna, SP and Monte Mor, SP) were more susceptible than the reference pathern used by the World Health Organization. The presence of three resistant house fly populations to cyromazine in Brazilian poultry farms strongly suggests that the operational aspects of larvicide use are important for the resistance development. Cyromazine is applied as a feed-through, both in Brazil and in the USA, where resistance has already been documented. However, in Denmark, where it was approved only as a topical manure spray, no case of resistance has yet been detected.